Understanding the Role of SARS-CoV-2 ORF3a in Viral Pathogenesis and COVID-19 - Zhang, Jiantao; Ejikemeuwa, Amara; Gerzanich, Volodymyr; Nasr, Mohamed; Tang, Qiyi; Simard, J. Marc; Zhao, Richard Y. (Frontiers in Microbiology, 2022)
The ongoing SARS-CoV-2 pandemic has shocked the world due to its persistence, COVID-19-related morbidity and mortality, and the high mutability of the virus. One of the major concerns is the emergence of new viral variants that may increase viral transmission and disease severity. In addition to mutations of spike protein, mutations of viral proteins that affect virulence, such as ORF3a, also must be considered. The purpose of this article is to review the current literature on ORF3a, to summarize the molecular actions of SARS-CoV-2 ORF3a, and its role in viral pathogenesis and COVID-19. ORF3a is a polymorphic, multifunctional viral protein that is specific to SARS-CoV / SARS-CoV-2. It was acquired from β-CoV lineage and likely originated from bats through viral evolution. SARS-CoV-2 ORF3a is a viroporin that interferes with ion channel activities in host plasma and endomembranes. It is likely a virion-associated protein that exerts its effect on the viral life cycle during viral entry through endocytosis, endomembrane-associated viral transcription and replication, and viral release through exocytosis. ORF3a induces cellular innate and pro-inflammatory immune responses that can trigger a cytokine storm, especially under hypoxic conditions, by activating NLRP3 inflammasomes, HMGB1 and HIF-1α to promote the production of pro-inflammatory cytokines and chemokines. ORF3a induces cell death through apoptosis, necrosis and pyroptosis, which leads to tissue damage that affects the severity of COVID-19. ORF3a continues to evolve along with spike and other viral proteins to adapt in the human cellular environment. How the emerging ORF3a mutations alter the function of SARS-CoV-2 ORF3a and its role in viral pathogenesis and COVID-19 is largely unknown. This review provides an in-depth analysis of ORF3a protein’s structure, origin, evolution and mutant variants, and how these characteristics affect its functional role in viral pathogenesis and COVID-19.